Comparative Morphology and DNA Evidences Between Dioscorea hispida Dennst. var. hispida and D. hispida - ทัพใหญ่, เชิดศักดิ์; นาคขุนทด, มลิวรรณ (KKU Science Journal, 2016)
Comparative morphology of Dioscorea hispida var. hispida and D. hispida var. neoscaphoides was studied by field and herbarium specimens investigation. The result showed that mostly vegetative and reproductive parts such as tuber, stem, leaf, bulbil, flower, fruit and seed, between two varieties were significant distinction. Moreover, shape of tepal, as well as hair and spine density were also different. On the other hand, the result of DNA study was indicated that D. hispida var. hispida and D. hispida var. neoscaphoides were not distinguished from each other based on only rbcL sequences. Therefore, only the information of morphological study were highly supported their variety status but couldn’t state var. neoscaphoides up to the specific rank.